Growth response of Dendrocalamus asper on elevational variation and intra-clump spacing management - Aqmal Nur Jihad; Budiadi Budiadi; Widiyatno Widiyatno (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Growth response of Dendrocalamus asper on elevational variation and intra-clump spacing management. 2021. Title. Biodiversitas 22: 3801-3810. Dendrocalamus asper (Schult. Schult. F.) Backer Ex. K. Heyne is a well-known commodity classified as a non-timber forest product (NTFP) to substitute wood-based products in the future. While bamboo is widely distributed in various habitats, and it could impact growth performance and quality. Nevertheless, the development of bamboo research on the upstream level is quite rare, specifically for clumping bamboo species. Therefore, our study aimed to reveal the performance in elevational variation and to discover the intra-clump spacing and diameter relationship. The elevational variation was divided into three levels, which were lower, middle, and higher levels. Each elevation was established in 9 plots with parameters observed were culm diameter at breast height (DBH), culm height (H), and culm volume (V) of D. asper. The intra-clump spacing was used to assess the relationship between the clump density and diameter growth. The research is complemented with in-depth interviews to explore the traditional silvicultural practices of Dendrocalamus asper and spatial analysis to generate land surface temperature and soil moisture index. The result showed that there is no effect (P > 0.05) of elevational variation to D. asper growth and development, while the availability of intra-clump spacing showed a significant result (P < 0.05) on the culm DBH of D, asper. Furthermore, our result suggests a wider intra-clump spacing (0.4-0.6 m2) is more recommended than a narrow intra-clump spacing for optimal culm diameter growth. Additionally, bamboo plantation was still less managed and utilized. Therefore, improving the productivity of D. asper by maintaining plantation, i.e., fertilizing, managing spacing among clump bamboo, and harvesting to achieve sustainable development of the bamboo plantation is useful.